Effects of sub-bituminous coal on boiler performance - Samsudin, Salmi (2017)
In Malaysia, coal-fired generation represents about one-third of the installed power generation capacity and accounted for nearly 43% of the electricity produced in 2014. Due to low cost in power generation, most of the developing countries use coal as the main fuel at power generation plants. During commissioning stage, boiler operation will be designed and tuned as per coal specification and environmental requirement factors. With limited source of coal for sub-critical boiler, this study measure the available coal that can be used. However, coal with different characteristic will affect the boiler performance and parameters. The objective of the study is to analyze the boiler operation performance, boiler efficiency, energy losses which is accomplished during combustion process which used from sub-bituminous coal as the main fuel. The best coal will be determined during the study and can be chosen to replace the existing coal by considering the results. The study was performing at a thermal coal power plant which has sub-critical boiler, reheat and coal fired boilers with a nominal rated power output of 700MW. The technical specification of the boiler includes the specification of main-steam piping, cold reheat steam piping and hot reheat steam piping. The boiler concepts are two-pass type boiler and drum with control circulation. During the study, numerical plant performance data was extracted from the data logging system for the whole period and presented in graphical view showing the pattern. Boiler efficiency was measured using direct method and indirect method, was found that coal with different Calorific Value (CV) and properties give different efficiency values to the boiler. The results show the sub-bituminous coal with CV 5013 kcal/kg similarly perform similar to designated coal with CV 4852 kcal/kg. Besides that, the superheated steam and reheater steam for coal CV 5013kcal/kg perform at normal value which is close to 540°C setting point. The desuperheater spray water flows operate between 18-25 t/h with minimal operational to achieve the target value, 540°C. The metal temperatures for superheated and reheater tube still within limit value, 550°C. In addition, the results convey the properties of coal contribute to the major energy losses during the combustion process in the furnace.